A game of two? Gene expression analysis of brain (cyp19a1b) and gonadal (cyp19a1a) aromatase in females of a Neotropical cichlid fish through the parental care period and removal of the offspring - Ramallo, Martín Roberto (2017)
For many species parental behavior is essential for the survival of the offspring. While the ultimate causes of teleost parental behavior have been widely studied, comparatively little is known about its proximate causes. The aim of this study was to analyze the yet unexplored, potential dual role of brain and gonadal aromatases, the enzymes responsible for the conversion of androgens to estrogens in the brains and gonads of teleosts, respectively, on the different stages of the maternal care period of the biparental cichlid Cichlasoma dimerus, locally known as chanchita. By immunohistochemistry we analyzed the neural distribution of brain aromatase and observed it exclusively within the forebrain, including areas involved in the regulation of parental behavior. We next analyzed the gene expression of brain aromatase in the brain, and gonadal aromatase in the ovary, of female chanchitas through the parental care period. To further characterize the physiological environment associated to maternal care, we also evaluated sex steroid levels (17β-estradiol, testosterone and 11-ketotestoterone) and ovarian follicle percentage. The onset of parental behavior specifically downregulated sex steroids synthesis and the rate of ovarian maturation, as denoted by a more than 10-fold decrease in steroid levels and delayed detection of mature follicles in females with offspring, compared to females which eggs were removed. Gene expression levels of both aromatases were independent of maternal care at the evaluated time points, even though they varied during the parental care period.